Reactions of provitamin‑a‑enriched maize to foliar diseases under field conditions in Nigeria (2023)
Maize is a major staple food in Sub-Saharan Africa (SSA). Vitamin A deficiency index is high in Africa and could be reduced through the consumption of provitamin-A-enriched maize. However, foliar diseases such as maize streak virus, northern corn leaf blight and common rust constrain maize production in SSA. The cultivation of host-resistant varieties is the most effective approach to mitigate their effects. Therefore, maize synthetics improved for PVA carotenoids, their selection cycles and crosses as well as a commercial disease-resistant check were assessed for resistance to maize streak virus, northern corn leaf blight and common rust at hotspots in Nigeria. The foliar diseases’ effects on the agronomic performance and carotenoid content of the maize genotypes were assessed. The Genotypes differed for most agronomic traits and foliar disease resistance. Stepwise regression revealed that, although the agronomic traits determined 93% of the grain yield, each foliar disease had effect on the yield. A unit increase in maize streak virus score increased plant aspect and husk cover scores by 0.6 and 0.4, respectively, whereas an increase in common rust score decreased plant height by 16.2 cm and increased plant aspect score by 0.7. Maize streak virus and common rust decreased genotypic variability for lutein by 36.7 and 18.7%, respectively, while northern corn leaf blight decreased genotypic variability for provitamin A by 27.1%. Most of the genotypes exhibited moderate susceptibility to northern corn leaf blight. However, three selection cycles and three crosses exhibited high tolerance to maize streak virus and moderate tolerance to common rust, thus can serve as sources of PVA-enriched, maize streak virus and common rust tolerant lines.